Consumption as a Growth Factor of the Russian Economy - Gulnaz F. GALIEVA; Luiza I. IL`INA; Sergey V. PONOMAREV; Bella O. KHASHIR; Evgeniya K. KARPUNINA (Communications of International Proceedings, 2020)
The purpose of the research is to study the role of consumption in the processes of ensuring economic dynamics and social development and to reveal the specifics of consumption of the Russian population in the period 2013-2018, as well as to identify existing contradictions. The authors made international comparisons and revealed a low share of final household consumption in Russia's GDP in comparison with similar indicators of developed consumer society models in the leading countries of the world. The authors studied the Russian dynamics of changes in the structure of GDP by expenditure. The article analyzes the conditions and factors that determine the structure of final consumption of households in Russia. It is determined that the structure of consumption in Russia is characterized by an extremely low share of services in comparison with developed countries and rapidly developing BRICS countries.  It is proved that the decrease in final consumption in the period 2015-2017 is due to a drop in real disposable income of the population and a reduction in personal consumption opportunities.
Keywords: Consumption; GDP; household expenditure; final household consumption; income inequality; Russia